Oxygenated hypothermic machine perfusion after static cold storage improves endothelial function of extended criteria donor livers. Issue 6 (June 2017) - Burlage, Laura C.; Karimian, Negin; Westerkamp, Andrie C.; Visser, Nienke; Matton, Alix P.M.; van Rijn, Rianne; Adelmeijer, Jelle; Wiersema-Buist, Janneke; Gouw, Annette S.H.; Lisman, Ton; Porte, Robert J.
Abstract: Background: Lack of oxygen and biomechanical stimulation during static cold storage (SCS) of donor livers compromises endothelial cell function. We investigated the effect of end-ischemic oxygenated hypothermic machine perfusion (HMP) on endothelial cell function of extended criteria donor (ECD) livers. Methods: Eighteen livers, declined for transplantation, were transported to our center using static cold storage (SCS). After SCS, 6 livers underwent two hours of HMP, and subsequent normothermic machine perfusion (NMP) to assess viability. Twelve control livers underwent NMP immediately after SCS. mRNA expression of transcription factor Krüppel-like-factor 2 (KLF2), endothelial nitric oxide synthase (eNOS), and thrombomodulin (TM) was quantified by RT-PCR. Endothelial cell function and injury were assessed by nitric oxide (NO) production and release of TM into the perfusate. Results: In HMP livers, mRNA expression of KLF2 (p = 0.043), eNOS (p = 0.028), and TM (p = 0.028) increased significantly during NMP. In parallel, NO levels increased during NMP in HMP livers but not in controls. At the end of NMP cumulative TM release was significantly lower HMP livers, compared to controls (p = 0.028). Conclusion: A short period of two hours oxygenated HMP restores endothelial cell viability after SCS and subsequent normothermic reoxygenation of ECD livers.